2007
DOI: 10.1007/s10549-007-9821-3
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 (Leu10Pro), p53 (Arg72Pro) can predict for increased risk for breast cancer in south Indian women and TGFβ1 Pro (Leu10Pro) allele predicts response to neo-adjuvant chemo-radiotherapy

Abstract: The breast cancer incidence has been increasing in the south Indian women. A case (n=250)-control (n=500) study was undertaken to investigate the role of Single Nucleotide Polymorphisms (SNP's) in GSTM1 (Present/Null); GSTP1 (Ile105Val), p53 (Arg72Pro), TGFbeta1 (Leu10Pro), c-erbB2 (Ile655Val), and GSTT1 (Null/Present) in breast cancer. In addition, the value of the SNP's in predicting primary tumor's pathologic response following neo-adjuvant chemo-radiotherapy was assessed. Genotyping was done using PCR (GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
4
29
1
Order By: Relevance
“…Association studies on other cancer types, for example, colorectal cancer [15], lung cancer [16], and head and neck cancer [28], also suggested that the variant was a relatively high-penetrant risk factor for developing cancer. In our present meta-analysis, IVS3 An assessment for Hardy-Weinberg equilibrium test identified that six studies on codon 72 [14,21,23,[29][30][31], one study on IVS3 16 bp Del/Ins [17], and one study on IVS6 ? 62A [ G [32] departed from HWE.…”
Section: Discussionmentioning
confidence: 76%
“…Association studies on other cancer types, for example, colorectal cancer [15], lung cancer [16], and head and neck cancer [28], also suggested that the variant was a relatively high-penetrant risk factor for developing cancer. In our present meta-analysis, IVS3 An assessment for Hardy-Weinberg equilibrium test identified that six studies on codon 72 [14,21,23,[29][30][31], one study on IVS3 16 bp Del/Ins [17], and one study on IVS6 ? 62A [ G [32] departed from HWE.…”
Section: Discussionmentioning
confidence: 76%
“…On the contrary many studies have reported no significant association between this SNP and breast cancer risk (Krippl et al, 2003;Jin et al, 2004;Saha et al, 2004;Cox et al, 2007b;Rajkumar et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…A total of thirty-one research articles involving 24021 cases and 31820 controls were finally included in the present meta-analysis based on our selection (inclusionexclusion) criteria (Ziv et al, 2001;Dunning et al, 2003;Hishida et al, 2003;Krippl et al, 2003;Quarmby et al, 2003;Jin et al, 2004;Le Marchand et al, 2004;Saha et al, 2004;Shu et al, 2004;Kaklamani et al, 2005;Lee et al, 2005;Shin et al, 2005;Feigelson et al, 2006;Scola et al, 2006;Cox et al, 2007a;2007b;Gonullu et al, 2007;Rajkumar et al, 2008;Chen et al, 2011;Joshi et al, 2011;Pooja et al, 2013) (Figure 1). The major characteristics of selected studies are summarized in Table 1.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Table 1 listed the main characteristics and genotype distribution of codon 72 polymorphism (rs1042522), with a total of 56 eligible studies met the inclusion criteria, including first author, published year, ethnicity, original country, source of controls, and genotype distribution. However, the study of Pharoah et al [50] and the study of Samson et al [51] were excluded because subjects had been included by Baynes et al [38] and Rajkumar et al [44]. The distribution of genotypes in the controls was consistent with Hardy-Weinberg equilibrium in all studies except for two studies (P \ 0.01) [21,65], these studies were excluded in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%